2001
DOI: 10.2460/javma.2001.218.1449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indications for use of fresh frozen plasma in dogs: 74 dogs (October through December 1999)

Abstract: Results suggest that FFP plays an important role in the care of critically ill dogs. Because the supply of FFP is limited, guidelines for when administration of FFP may be clinically useful should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…Administering a hyperoncotic solution can alter the transcapillary fluid dynamic and may result in edema due to fluid overload. 16,41,42 It has also been suggested that supraphysiologic infusions of albumin could increase the risk of hypersensitivity reactions to albumin. 36 The slow, incremental nature of CRI allows immediate discontinuation of administration should severe reactions occur, compared with a bolus, where the entire volume might have been administered before a reaction is detected.…”
Section: Discussionmentioning
confidence: 99%
“…Administering a hyperoncotic solution can alter the transcapillary fluid dynamic and may result in edema due to fluid overload. 16,41,42 It has also been suggested that supraphysiologic infusions of albumin could increase the risk of hypersensitivity reactions to albumin. 36 The slow, incremental nature of CRI allows immediate discontinuation of administration should severe reactions occur, compared with a bolus, where the entire volume might have been administered before a reaction is detected.…”
Section: Discussionmentioning
confidence: 99%
“…When whole blood is centrifuged to produce plasma and PRBCs, the anticoagulant segregates with the plasma fraction. 75,87 Calculations suggest 45 mL/kg of plasma would need to be given to increase albumin serum concentration by 1 g/dL. 121 Fresh frozen plasma maintained in an upright freezer at À20 C maintains clotting factor activity for 6 months.…”
Section: Fresh Frozen Plasmamentioning
confidence: 99%
“…The use of fresh-frozen plasma (10-15 mg/kg once daily) is recommended by some authors in dogs with severe pancreatitis because it contains useful components, such as protease inhibitors (e.g., α 1 -proteinase inhibitor, α 2macroglobulin), albumin, and both coagulation and antithrombotic factors (Williams 1996;Logan et al 2001). Protease inhibitors are believed to protect from the development or worsening of pancreatitis, and depletion of protease inhibitors has been reported in dogs with both experimental and spontaneous pancreatitis Williams 1996;Ruaux & Atwell 1999).…”
Section: Plasma and Blood Transfusionmentioning
confidence: 99%